Confronting Students' Personal and Interpersonal Communication Anxieties and Needs through Constitutive, Experiential Communication Pedagogy - Lawrence R. Frey; Emily Loker (Central States Communication Association, 2020)
Today's college students are experiencing unprecedented high levels of anxiety, resulting in devastating effects. This essay challenges communication educators to respond directly to this significant issue by employing an experiential pedagogy that offers students constitutive opportunities to initiate, experiment with, and receive feedback about new communicative behaviors that will enable them to interact well and achieve positive outcomes in high anxiety-inducing interactions. The essay explicates how that constitutive, experiential pedagogy informs the course "Communication and Human Relations," enabling students to acquire communication competencies to reduce their anxiety about and to manage effectively their personal and interpersonal communication difficulties.